Influence of cyclic loading on lightweight self-compacting concrete double-skin tubular columns - Khaled Mohamed Elhadi; Mohamed Hechmi El Ouni; Muhammad Arshad; Ali Raza; Muhammad Abid; Ahmed Farouk Deifalla (Alexandria Engineering Journal, 2023)
Self-compacting concrete (SCC) has gained prominence in recent decades due to its inherent qualities, particularly its ability to compact autonomously. SCC proves invaluable in scenarios where traditional compaction is challenging due to placement conditions or the presence of close space reinforcement. This study focuses on evaluating the structural performance of lightweight self-compacting concrete (LWSCC) columns confined with glass fiber-reinforced polymer (GFRP) and steel tube (ST) subjected to cyclic loading. The LWSCC columns, denoted as LWSTC, are designed with inner steel tubes and outer GFRP tubes, imparting corrosion resistance and reduced weight alongside enhanced ductility. Through quasi-static loading, five fabricated LWSTC columns were subjected to assess their structural response under dynamic effects. The investigation delves into three key variables: axial load ratio, reinforcement ratio, and the replacement ratio of coarse lightweight expanded clay aggregate (LECA) in the fabricated LWSTC columns. A comprehensive analysis of various parameters, including skeleton curves, ductility, hysteretic cycles, damage modes, dissipation of energy capacity, stiffness behavior, strain spreading, and strength reduction, was conducted on the LWSTC columns. The findings reveal that the replacement of LECA with natural aggregates has an insignificant impact, whereas varying the axial load ratio significantly influences the structural behavior of LWSTC. Notably, LWSTC exhibits a remarkable 121% higher horizontal load capacity compared to counterparts using natural aggregate. Furthermore, LWSTC demonstrates superior axial strength and enhanced capability for energy dissipation.